2013
DOI: 10.4236/pp.2013.42021
|View full text |Cite
|
Sign up to set email alerts
|

A Possible Mechanism of Cisplatin-Induced Tumor Necrosis Factor (TNF)-α Production in Murine Macrophages

Abstract: Cisplatin has been used for the treatment of various solid cancers or sarcomas; however, it can induce severe adverse effects. Among these adverse effects, nephrotoxicity, which has the potential to be a dose-limiting factor of this agent, develops due to the secretion of tumor necrosis factor-α (TNF-α) from macrophages; however, the precise mechanisms are still unclear. To elucidate possible mechanisms, we investigated the involvement of mitogen-activated protein kinases (MAPK) and reactive oxygen species (RO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Since the addition of DMTU resulted in a significant decrease in the percentage of dead cells and did not increase the percentage of early apoptotic cells, we can deduce that DMTU plays the protective role for cells treated with cisplatin. The results are consistent with works of other researches showing the ability of DMTU to reduce the accumulation of singlet oxygen, hydroxyl radical [17], H 2 O 2 [18], and block the activation of p53, leading to weakening of p53 upregulated modulator of apoptosis alpha (PUMA-α) production and suppression of the mitochondrial pathway of apoptosis during cisplatin treatment [16,21].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Since the addition of DMTU resulted in a significant decrease in the percentage of dead cells and did not increase the percentage of early apoptotic cells, we can deduce that DMTU plays the protective role for cells treated with cisplatin. The results are consistent with works of other researches showing the ability of DMTU to reduce the accumulation of singlet oxygen, hydroxyl radical [17], H 2 O 2 [18], and block the activation of p53, leading to weakening of p53 upregulated modulator of apoptosis alpha (PUMA-α) production and suppression of the mitochondrial pathway of apoptosis during cisplatin treatment [16,21].…”
Section: Discussionsupporting
confidence: 92%
“…For this purpose, in this study, we employed ROS scavenger N,N'-dimethylthiourea (DMTU). DMTU is a highly efficient absorber of OH • , 1 O 2 [16,17], and H 2 O 2 [18], known to decrease the H 2 O 2 -induced damage of cultured endothelial cells [19], to reduce the cisplatin-induced tumor necrosis factor-alpha (TNF-α) expression in macrophages in vitro, and to prevent the development of oxidative stress, activation of p53 and, as a consequence, apoptosis of renal and hepatic cells in vivo [20][21][22][23]. An important step is to carry out experiments on cytotoxicity of cisplatin under conditions of hydrogen peroxide removal from cells using DMTU.…”
Section: Experimental Investigationsmentioning
confidence: 99%
“…Previous studies showed that TNFa expression and secretion from macrophage and head and neck squamous cell cancer can be induced by cisplatin (16,17). Altogether, our observations suggest that platinum derivative chemotherapy could increase TNFa production levels in the tumor microenvironment and inflammation, and might sustain tumor development and/or progression.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that TNFa expression and secretion from macrophage and some cancer cell lines can be induced by platinum derivative (cisplatin; refs. 16,17). OXA plus 5-fluorouracil (5-FU) and folinic acid (referred to as Folfox) or IRI plus 5-FU and folinic acid (referred to as Folfiri) are the standard treatments used to treat advanced colon cancer but also other types of cancer.…”
Section: Chemotherapeutic Drugs Induce Endogenous Tnfa Productionmentioning
confidence: 99%
“…TNF-α, secreted by activated neutrophile granulocytes and mononuclear macrophages, is a multi-functional polypeptide (6). It may stimulate inflammatory cells and produce toxic effects when associated with corresponding receptors; tissues eventually become severely damaged due to the increase in inflammatory factors, including IL-6 and IL-8 (7).…”
Section: Introductionmentioning
confidence: 99%